Unraveling the environmental Kuznets curve in IGAD countries: interplay between ecological footprint, economic growth, renewable energy, and globalization - Abdimalik Ali Warsame; Hudayfe Osman Daror; Abdulkadir Mohamed Abdullahi (Environmental Research Communications)
Climate change has become a global phenomenon; hence, mitigating environmental pollution and degradation are crucial for addressing climate change consequences. A paradigm shift from fossil fuel to clean energy sources is suggested to reduce environmental pollution without compromising economic growth. This study assesses the validity of the environmental Kuznets curve (EKC) hypothesis by incorporating the impacts of renewable energy, population density, and globalization on ecological footprint in IGAD member nations. A battery of econometric techniques, such as Pedroni, Kao, and Johansen Fisher cointegration methods, heterogeneous panel methods, and Dumitrescu-Hurlin panel causality tests are utilized. Before the formal analysis, we performed a cross-sectional dependence test; and it was observed that the data are cross-sectional dependent. Hence, the second-generation unit root test is utilized which confirms that all the interested variables are stationary at the first difference I (1). The empirical results of cointegration methods indicate that explanatory variables are cointegrated into the ecological footprint in the long run. Moreover, the PMG—which provides consistent results as evidenced by the Hausman test—underscored that globalization, population density, and renewable energy mitigate ecological footprint in the long run even though renewable energy is insignificant. An increase in economic growth is associated with a deterioration of environmental pollution, while squared growth is linked to a reduction in pollution. This evidence supports the existence of the EKC theory, which posits an inverted U-shaped relationship between economic expansion and ecological footprint. Besides, unidirectional causalities are detected from ecological footprint to population density, renewable energy, economic growth, and squared economic growth but not the other way around. In light of the empirical results, several policy recommendations are proposed.